Essential Public Health Functions (Revista Venezolana de Salud Pública, 2018)
The Essential Functions of Public Health (FESP) describe the spectrum of competencies and actions required by health systems to achieve the central objective, which is to improve the health of populations. The Pan American Health Organization, through the "Public Health in the Americas" Initiative, defined eleven (11) EPHF and developed an instrument to measure its performance, which allows countries to perform a self-assessment of their capacities to exercise public health. Special attention deserves, within this FESP, research in public health, health promotion, social participation as well as monitoring, evaluation and analysis of the health problems of the population. These functions are some of the central themes of the Venezuelan Public Health Journal, thus contributing, through its scientific articles, to disseminate and strengthen them. Similarly, the continuous dissemination of knowledge about these topics helps to influence other functions such as the training of human resources in collective health and in the surveillance, research and control of health problems.
Keywords: Funstions; essential functions; public health